Nyadran Ruwah Tradition as a Manifestation of Rationality in Nusantara Philosophical Thought - Sartini Sartini; Muhammad Rodinal Khair Khasri; Luwiyanto Luwiyanto (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
The rationality of Nyadran as a cultural and philosophical Nusantara phenomenon needs to be studied, including Nyadran at Kemloko. The research aims to explain the Nyadran tradition, history, and the rationality of society. The data was collected by observation, interviews, literature review. We conducted observations of Nyadran practitioners in Kemloko hamlet, Temanggung, Central Java, and carried out in-depth interviews using purposive sampling based on key figures involved in the implementation of Nyadran in Kemloko. The data were examined through the lens of cultural rationality, which combines cultural and rational choice perspectives to explain behavior in political and social contexts. The results of the study, first, Nyadran in Kemloko was carried out in the months of Ruwah and Rajab, the month before Ramadan, coinciding with Friday. Kenduri Nyadran is performed at home or tomb and its implementation develops according to community conditions. Second, Nyadran has existed since the pre-Majapahit era and has grown to this day. Third, the implementation of Nyadran is based on traditional, affective, instrumental rationality and value rationality. Nyadran is an act of following the traditions of parents and ancestors. Affectionately, Nyadran is a proof of respect, obedience and devotion, as well as self-melting in society. Nyadran instrumentally becomes a means of showing devotion, a means of praying, a means of socializing, and a means of entertainment. The values contained in Nyadran are considered not to conflict with religious values and goodness in local culture.